WORDWALL SEBAGAI MEDIA PEMBELAJARAN ALJABAR DALAM MATEMATIKA BILINGUAL UNTUK SISWA SEKOLAH DASAR: WORDWALL AS A LEARNING MEDIA FOR ALGEBRA IN BILINGUAL MATHEMATICS FOR ELEMENTARY SCHOOL STUDENTS - Rusani, Irna; ria, ria kilala; Rakhmawati, Astri; Situmorang, Helena (KAMBIK: Journal of Mathematics Education, 2025)
This study aims to analyze the effect of using the Wordwall application as a learning medium in bilingual-based algebra mathematics learning at SD YPK 2 Immanuel Kampung Baru. This study used a qualitative descriptive method with data obtained through observation, documentation, and interactive quizzes. The research process included the preparation of bilingual materials, the implementation of learning using Wordwall, and data collection. The results showed that Wordwall was effective in increasing students' motivation, engagement, and understanding of algebra material. Based on the quiz results, active male and active female students showed high engagement and good understanding of algebra and English. Meanwhile, moderately active students, both male and female, showed moderate engagement with some obstacles in English mastery. The findings also revealed that the visual and audio features in Wordwall helped students with diverse language abilities to remain actively involved. This study concluded that the integration of gamification-based technology, such as Wordwall, can be an innovative approach to improving the quality of learning in the digital era.